Agency at the Time of the Anthropocene - Latour, Bruno (New literary history, 2014)
Among the many problems raised by political ecology is one of language. The distribution between what is inert object and what is made of talking subjects does not do justice to science nor to literature—nor, of course, to politics. Hence, an effort to describe a relation with agency that focuses not on their characters (humans or nonhumans, animated or deanimated) but rather on their common source. This source is recognized here—both semiotically and then ontologically—as a “metaphorphic zone.” It is just such a common articulation that could allow speaking with and about former “facts of nature” in a different way, a way better adjusted to the new political situation.